Gender Differences in the Factors Associated withAlcohol Binge Drinking: A Population-Based Analysis ina Latin American Country - Hernández-Vásquez, Akram (2022)
Alcohol consumption is a public health problem in Peru, fostered by traditional practices,where promoting social interaction in celebrations, facilitating field work as a source of energy andwarmth, and achieving objectives in certain labor negotiations, play an important role. However,research on the risk factors of binge drinking according to gender is limited. The study aim was todetermine the factors associated with binge drinking in the Peruvian adult population by gender.An analytical study of secondary data from the 2018 Peruvian Demographic and Family HealthSurvey was conducted. The dependent variable was binge drinking in the last 30 days. Adjustedprevalence ratios (aPR) were estimated for the association between sociodemographic and health-related variables with binge drinking. A total of 32,020 adults were included. Binge drinking wasfound in 22.4%. Men (32.6%; 95% confidence interval [CI]: 31.4–33.8) presented a higher consumptionpattern compared to women (12.8%; 95% CI: 12.0–13.6). For both genders, differences were found inbinge drinking according to sociodemographic characteristics (age and wealth quintile was associatedin both genders while the educational level was associated only for men, and ethnic self-identificationand marital status for women) and health- characteristics related (health insurance, smoking in thelast 30 days, overweight and obesity were associated in both genders). Several factors are associatedwith binge drinking according to gender in the Peruvian population, including age and educationlevel among men, as well as marital status and ethnic self-identification among women.